Capillary Problem and Mean Curvature Flow of Killing Graphs - Wanderley, Gabriela Albuquerque (2013)
We study two types of Neumann problem related to Capillary problem and to the evolution of graphs under mean curvature flow in Riemannian manifolds endowed with a Killing vector field. In particular, we prove the existence of Killing graphs with prescribed mean curvature and prescribed boundary conditions.